A QUANTITATIVE STUDY OF BRAND AWARENESS, BRAND ASSOCIATION, AND BRAND IMAGE IN THE IMPROVEMENT OF BRAND EQUITY FOR SMARTPHONE INDUSTRY IN SEMARANG - Fathurachman, Chadyan (Stability: Journal of Management and Business, 2024)
The background of the research came from the top brands of smartphones. The smartphone industry filled with many companies, which Apple is in the second behind Samsung as the first position. To take the first position, Apple has to build a strategy to be the top brand of smartphone in Indonesia. The objective of the study is to assess the impact of brand awareness, brand association, and brand image towards the brand equity.The sample population in the research is not precisely known, implementing MOE formula to gain 96 respondents. The sample collection is implementing purposive sampling. The analysis method implementing multiple linear regression. The result shows that brand awareness has impacting role towards brand equity, brandÂ  association has impact towards brand equity. Brand image has impact towards brand equity. Brand image become the most dominant variable in affecting brand equity with 0.360 regression score